Divergence-preserving alternating direction implicit scheme for multi-pole debye dispersive media - Heh, Ding Yu (2020)
This letter presents the formulation of divergence-preserving alternating direction implicit (DP-ADI) scheme for multi-pole Debye dispersive media. The analytical proof of divergence-preserving property of the scheme in Debye media is provided. Numerical results of modeling human skin as Debye media further validate our proposed scheme.